Fluctuating Asymmetry and Length-Weight Relationship of the Three Populations of Sardinella lemuru (Clupeiformes, Dorosomatidae) from Surigao del Norte, Philippines - Cinco, J. G.; Farma, J.; Silvosa, J. D.; Weling, C. B.; Cuadrado, J. T. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2023)
Despite its economic importance and current conservation status, studies on Sardinella lemuru (Bleeker, 1853) are very scarce in the province of Surigao del Norte, Philippines, so this study was conducted to assess the body shape and health status of fish populations in the area using fluctuating asymmetry (FA) and length-weight ratio (LWR) analyses. 258 individuals were collected from the coastal waters of Malimono (n = 6), San Francisco (n = 101) and Surigao (100) from August to October 2021 using fishnets and gillnets. Among the three populations, fish samples from Malimono have the highest cumulative variation of 63.07 % followed by San Francisco and Surigao City (60.85 % and 55.51 %). The high percentage of FA among the three populations (57.66 % in Malimono; 54.43 % in San Francisco; and 49.78 % in Surigao City) also suggests that individuals had deformities particularly, especially in the fins and head region of the fish. The LWR of the fish samples (b = 2.6398 in Malimono; b = 2.7541 in San Francisco; and b = 2.8377 in Surigao City) indicates a negative allometric growth pattern, suggesting that the fish samples do not grow symmetrically or become thinner with increasing length. The results of FA and LWR analyses suggest morphological abnormalities in the fish samples that may be attributed to the different environmental stressors in the area. Studies on sex differences, water quality and fish ecology are suggested to better understand the current status of fish in the area.